Disparate bilingual experiences modulate task-switching advantages: A diffusion-model analysis of the effects of interactional context on switch costs - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2016)
Drawing on the adaptive control hypothesis (Green & Abutalebi, 2013), we investigated whether bilinguals' disparate interactional contexts modulate task-switching performance. Seventy-five bilinguals within the single-language context (SLC) and 58 bilinguals within the dual-language context (DLC) were compared in a typical task-switching paradigm. Given that DLC bilinguals switch between languages within the same context, while SLC bilinguals speak only one language in one environment and therefore rarely switch languages, we hypothesized that the two groups' stark difference in their interactional contexts of conversational exchanges would lead to differences in switch costs. As predicted, DLC bilinguals showed smaller switch costs than SLC bilinguals. Our diffusion-model analyses suggest that DLC bilinguals' benefits in switch costs are more likely driven by task-set reconfiguration than by proactive interference. Our findings underscore the modulating role of the interactional context of conversational exchanges in task switching.